Literacy Education of Halal Products to Forming Youth Entrepreneurs at The Sirojul Huda Islamic Boarding School, Bogor, West Java - Sufyati HS; Fadhli Suko Wiryanto; Yudi Nur Supriadi (LPPM Universitas Muhammadiyah Tasikmalaya, 2023)
Islamic boarding schools are Islamic educational institutions that seek to educate their students to always live by following Islamic law. Based on Law No. 18 of 2019 concerning Islamic boarding schools, Islamic boarding schools function as educational institutions, da'wah, and community empowerment. Islamic boarding schools, as Islamic educational institutions, offer good opportunities to take advantage of the momentum in increasing the market trend of halal products by increasing entrepreneurship-based curricula and being able to collaborate with world industries. Halal product literacy is an important issue in entrepreneurship activities so that Muslim communities become safe and comfortable in consuming products, especially food and beverages as primary needs. This community service activity was carried out by UPN Veteran Jakarta academics and the Sirojul Huda Bogor Islamic Boarding School as partners. The target of this activity is students who are currently studying at the senior high school level at the Sirojul Huda Bogor Islamic Boarding School. The main problem is that the literacy level of Islamic boarding school students is still low, even though they have provided material about halal and haram law in Islam. The objectives of this PKM are (1) to provide education about the world of entrepreneurship by following the concept of Islamic sharia; (2) to provide education and socialization of the mechanism of halal-certified products; (3) increasing motivation and foster an entrepreneurial spirit by following the guidance of the Qur'an and Al Hadith; (4) preparing the students so that after graduation they can live competitively in society independently. The activity method used lectures and Focus Group Discussion (FGD). The results of these activities show that there is an increase in literacy of halal products and the concept of entrepreneurship by following Islamic law after socialization and education. These have to be carried out sustainably with collaboration and synergy between academics, boarding schools, and the world industry.